2019
DOI: 10.1016/j.sjopt.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of topical 0.03% Tacrolimus ointment in children with refractory vernal keratoconjunctivitis in Middle East

Abstract: Objective The purpose of this paper is to review the efficacy and safety profile in children treated with topical 0.03% Tacrolimus ointment for vernal keratoconjunctivitis in Middle East and to propose a treatment posology. According to recent studies, a complex non-IgE dependent mechanism plays a relevant role in the pathogenesis of vernal keratoconjunctivitis. Numerous cells and mediators have been found in the serum, conjunctiva and tears of patients with Vernal keratoconjunctivitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“… 16 , 17 In 2019, Fiorentini et al showed that tacrolimus eye ointment 0.03% can be used as a safe and effective agent for the treatment of refractory VKC in children. 18 IFN α-2b is a cytokine with anti-proliferative, anti-inflammatory and immunomodulator effects, which inhibits arachidonic acid metabolism, stabilises mast cells and inhibits IgE-mediated release of histamine. The role of IFN α-2b has been established in allergic asthma, atopic dermatitis and in conjunctival neoplasias.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 In 2019, Fiorentini et al showed that tacrolimus eye ointment 0.03% can be used as a safe and effective agent for the treatment of refractory VKC in children. 18 IFN α-2b is a cytokine with anti-proliferative, anti-inflammatory and immunomodulator effects, which inhibits arachidonic acid metabolism, stabilises mast cells and inhibits IgE-mediated release of histamine. The role of IFN α-2b has been established in allergic asthma, atopic dermatitis and in conjunctival neoplasias.…”
Section: Discussionmentioning
confidence: 99%
“…TAC is a non-steroidal immune-modulator capable of blocking the calcineurin, thereby suppressing the synthesis of different cytokines through active T cells. TAC ointment is extensively effective to treat atopic dermatitis (21). The topical TAC in doses of 0.02-0.1% are reportedly useful to treat multiple refractory inflammatory diseases of the eye surface, such as VKC and atopic keratoconjunctivitis (AKC) (28).…”
Section: Discussionmentioning
confidence: 99%
“…These two medications belong to calcineurin inhibitors capable of deactivating the T cells and relevant produced cytokines contributing to develop the VKC. The inhibitory activity of cyclosporin on the T cells is approximately 100 times less than that of TAC, thus the preparation of ophthalmic TAC can be stronger against the severe form of VKC (21)(22)(23)(24)(25). The present research aimed to investigate the safety and effectiveness of TAC suspension 0.05% on treatment of long standing refractory VKC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the routinely used mast cell inhibitor eye drops such as olopatadine or cromolyn sodium, resistant cases of ocular allergy have been shown to benefit from short-term topical steroids and long-term topical cyclosporine 0.5% or tacrolimus 0.03%, as these are involved in blocking the IgE-mediated cellular (T-cell) activation. [ 74 95 96 ] Controlling IgE levels are also considered important in the management of KC. For patients with high IgE, Ahuja et al .…”
Section: Arkers In O Cular a Ll...mentioning
confidence: 99%